The Impact Of Industrial Labor On Achieving Net Value Added For The Industrial Sector And Small Industrial Projects In Syria - Kabakly, Ebtehal; Moualla, Hadeel (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to shed light on the reality of small industrial projects in particular and the reality of the industrial sector in general through studying the relative importance of small projects in industry and the impact of employment on achieving net output in each of them, This can be achieved through the study of several indicators: 1-first indicator: Ratio of small industrial projects contribution in the industrial net output in the cost of production factors. 2-second indicator: Ration of small industrial projects contribution in employment of labor in the industrial sector. 3-third indicator: The correlation between the numbers of employees in small industrial projects as an independent variable and the industrial net output with cost factor in these projects as a dependent variable. 4-forth indicator: The correlation between the number of employees in the industrial sector as an independent variable and the industrial net output with cost factors as a dependent variable. And thus we can reach a set of results that show the effectiveness of the employment of workers in small industry and industrial projects in the composition of the net output and the most important problems that face it. In addition to presenting a set of proposals that could contribute to solving these problems. يهدف هذا البحث إلى دراسة الأهمية النسبية للمشروعات الصغيرة في الصناعة و أثر توظيف القوى العاملة في تحقيق الناتج الصافي لكل من المشروعات الصناعية الصغيرة بشكل خاص والقطاع الصناعي بشكل عام ، ويتم ذلك من خلال دراسة عدة مؤشرات: - المؤشر الأول: نسبة مساهمة المشروعات الصناعية الصغيرة في الناتج الصافي الصناعي بتكلفة عوامل الإنتاج. - المؤشر الثاني: نسبة مساهمة المشروعات الصناعية الصغيرة في تشغيل القوى العاملة في القطاع الصناعي. - المؤشر الثالث : العلاقة الارتباطية بين عدد العاملين في المشروعات الصناعية الصغيرة كمتغير مستقل والناتج الصافي الصناعي بتكلفة عوامل الإنتاج في هذه المشروعات كمتغير تابع. - المؤشر الرابع: العلاقة الارتباطية بين عدد العاملين في القطاع الصناعي كمتغير مستقل والناتج الصافي الصناعي بتكلفة عوامل الإنتاج كمتغير تابع. وبالتالي الوصول إلى مجموعة من النتائج التي تبين مدى فعالية تشغيل العاملين في المشروعات الصناعية والصناعية الصغيرة في تكوين الناتج الصافي وأهم المشكلات التي تعترض ذلك. بالإضافة لتقديم مجموعة من المقترحات التي من الممكن أن تساهم في حل هذه المشكلات.